Charley's Aunt, 1959 #03 - Missouri Southern State University (1959)
Galen Lewis, Jim Lobbey, Nancy Mapes, Estel Landreth, Rebecca Dooler, Dick Stevens, Judy Griffis, Jane Hillhouse, Jim Camp, Jim Pearl